DEVELOPMENT OF NANOPARTICLE FORMULATIONS LOADED WITH PHYTOCHEMICALS LIKE BERBERINE FOR ENHANCED ANTICANCER ACTIVITY - Pankaj Mohan Pimpalshende,; Sujith S Nair,; Shama Afroze Baig,; Suganthi P,; Shiwali Bisht,; Umadevi A,; Rangu Nirmala,; Ashish Bhanudas Wadekar, (The Bioscan, 2026)
The natural isoquinoline alkaloid Berberine (Brb) has strong multi-pathway anticancer activity which is severely limited by low aqueous solubility, rapid metabolism, and poor oral bioavailability. Purpose: The research paper assesses the design and effectiveness of several nanotechnology-based delivery systems that can be used to address these pharmacokinetic barriers.